Atributos do solo, crescimento inicial e teor de flavonoides em mudas de fava-danta sob níveis de saturação por bases - Cryslane Goncalves Cota (2017)
The fava-d'anta (Dimorphandra mollis Benth.) is a medicinal species, native to the cerrado, collected by local populations. Its main economic importance is in the fruit, from which the pharmaceutical industry extracts rutin and quercetin. The fruits are obtained by means of extractivism. Lack of knowledge and sustainable management has put the long-term survival of the species at risk. In view of the economic and medicinal potential of this species and the small number of information on aspects of mineral nutrition, the objective was to evaluate the influence of base saturation levels on the soil chemical attributes and the initial growth and the production of total flavonoids in seedlings of fava-d'anta. The work was conducted at Institute of Agrarian Sciences of UFMG, in a randomized block design with seven treatments: saturation by natural soil base (3%), and the other treatments with 10, 20, 30, 40, 50 and 60% of saturation with five replications. The increase of the base saturation was accomplished through the application of doses of calcium oxide and magnesium. The seeds used were submitted to dormancy overcoming with concentrated sulfuric acid for 1 hour and then treated with fungicide carbendazim 15% + thiram 35% and seeded in pots. After 130 days of sowing, measurements of height and collecting diameter were taken. Were still evaluated the dry matter of shoot and root, Dickson quality index (IQD), total flavonoid content, nutrient content and accumulation of shoot dry matter. The increase of the base saturation reflected in the improvement of soil chemical attributes by increasing the pH, of the CEC and concentrations of exchangeable cations Ca+2 and Mg+2, and reducing of exchangeable acidity, potential acidity and aluminum saturation. The height, dry biomass and total flavonoid content of fava-d'anta seedlings were not influenced by the increase in base saturation, however, there was a decrease in the collection diameter. Thus, the soil natural conditions of the Cerrado provide the best development of the species, evidencing its tolerance to soil acidity.